Angiotensin‐converting enzyme inhibitor prevents skeletal muscle fibrosis in diabetic mice. Issue 8 (20th June 2021) - Kakutani, Naoya; Takada, Shingo; Nambu, Hideo; Maekawa, Satoshi; Hagiwara, Hikaru; Yamanashi, Katsuma; Obata, Yoshikuni; Nakano, Ippei; Fumoto, Yoshizuki; Hata, Soichiro; Furihata, Takaaki; Fukushima, Arata; et al.
Abstract : New Findings: What is the central question of this study? We questioned whether an angiotensin‐converting enzyme (ACE) inhibitor prevents skeletal muscle fibrosis in diabetic mice. What is the main finding and its importance? Administration of ACE inhibitor prevents the increase in skeletal muscle fibrosis during the early phase after induction of diabetes by streptozotocin. Our findings might provide a new therapeutic target for skeletal muscle abnormalities in diabetes. Abstract: Fibrosis is characterized by the excessive production and accumulation of extracellular matrix components, including collagen. Although the extracellular matrix is an essential component of skeletal muscle, fibrosis can have negative effects on muscle function. Skeletal muscle fibrosis was shown to be increased in spontaneously hypertensive rats and to be prevented by an angiotensin‐converting enzyme (ACE) inhibitor, an antihypertensive drug, in dystrophic mice or a mouse model of myocardial infarction. In this study, we therefore analysed whether (1) there is increased skeletal muscle fibrosis in streptozotocin (STZ)‐induced diabetic mice, and (2) a preventive effect on skeletal muscle fibrosis by administration of an ACE inhibitor. Skeletal muscle fibrosis was significantly increased in STZ‐induced diabetic mice compared with control mice from 2 to 14 days post‐STZ. The ACE inhibitor prevented both skeletal muscle fibrosis and the reduction in muscle function in STZ‐treated mice. Our study demonstrated that administration of an ACE inhibitor prevents the increase in skeletal muscle fibrosis during the early phase after onset of diabetes. Our findings might provide a new therapeutic target for skeletal muscle abnormalities in diabetes. Future studies are required to clarify whether skeletal muscle fibrosis is also linked directly to physical activity. Abstract :